Kelembutan dalam Rumah Tangga sebagai Tanda Kebaikan: Studi Takhrij Hadis dan Pemaknaan dengan Pendekatan Psikologi - Mushlihati, Mushlihati; Hudaya, Hairul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
This research is motivated by the increasing number of divorces and cases of domestic violence in Indonesia. So this study aims to determine the quality of the hadith regarding gentleness in the household as a sign of goodness and understand its meaning with a psychological approach. This research uses a qualitative method with the type of literature study, the problems in this study are examined using a takhrij approach and the meaning of hadith within the scope of psychological discussion. The results obtained from this study are the first, the quality of the hadith about gentleness in the family is a sign of this goodness of valid quality (H.R Ahmad Number 24.427), this is illustrated by the results of takhrij conducted. Hadith sanad is continued and has fair and strong memorization of narrators, then the hadiths also do not conflict with the Qur'an, other traditions, reason, facts, and history. secondly, the meaning of this hadith when viewed from a psychological review is in line with the existing hadith, that gentleness is one of the characteristics of someone who has a meaningful personal life and this leads him to the gate of happiness. Thus, a gentle attitude both in the view of Islam and psychology is something that brings goodness and avoids a person from the negative impacts that occur due to communication that prioritizes the ego, especially in married relationships.